2018
DOI: 10.1039/c8fo00528a
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of stachyose contribution to the growth of Lactobacillus acidophilus CICC22162

Abstract: Stachyose is a functional oligosaccharide, acting as a potential prebiotic for colonic fermentation. To understand the mechanism of how stachyose promotes the growth of probiotic bacterium, we analyzed the differences of the proteome of Lactobacillus acidophilus grown on stachyose or glucose. By a combination of two-dimensional electrophoresis and mass spectrometry analysis, we observed 16 proteins differentially abundant under these two conditions and identified 9 protein spots. Six of these proteins were hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…[17] Several studies have reported that STA stimulates the growth of Lactobacillus and Bifidobacterium in the intestinal tract, inhibits enteric bacilli, and prevents intestinal damage. [18][19][20] The STA-enriched -Galactooligosaccharides stachyose could modulate the profile of intestinal microbiota and enhance the intestinal mucosal barrier function of fish. [21] Soybean oligosaccharides including STA promote cellular immunity, humoral immunity, nonspecific immunity, and immunoglobulin levels in mice.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Several studies have reported that STA stimulates the growth of Lactobacillus and Bifidobacterium in the intestinal tract, inhibits enteric bacilli, and prevents intestinal damage. [18][19][20] The STA-enriched -Galactooligosaccharides stachyose could modulate the profile of intestinal microbiota and enhance the intestinal mucosal barrier function of fish. [21] Soybean oligosaccharides including STA promote cellular immunity, humoral immunity, nonspecific immunity, and immunoglobulin levels in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in soy foods has increased with the rising awareness of its benefits on health among consumers because of the biological activity of dominant constituents such as stachyose and isoflavones [ 16 , 17 ]. Stachyose is tetrasccharide polymer with two alpha-D-galactosyl residue linked (1→6) to the D-glucosyl residue of sucrose ( Fig.…”
Section: Introductionmentioning
confidence: 99%